2016
DOI: 10.1158/1055-9965.epi-16-0147
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk Score Mendelian Randomization Shows that Obesity Measured as Body Mass Index, but not Waist:Hip Ratio, Is Causal for Endometrial Cancer

Abstract: Background The strongest known risk factor for endometrial cancer (EC) is obesity. To determine whether single nucleotide polymorphisms (SNPs) associated with increased body mass index (BMI) or waist-hip ratio (WHR) are associated with EC risk, independent of measured BMI, we investigated relationships between 77 BMI and 47 WHR SNPs and EC in 6,609 cases and 37,926 country-matched controls. Methods Logistic regression analysis and fixed-effects meta-analysis were used to test for associations between EC risk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
63
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 35 publications
17
63
3
Order By: Relevance
“…Similarly, the International Agency for Research on Cancer recently deemed adiposity to be causal for endometrial cancer . Furthermore, our findings are in partial agreement with recent Mendelian Randomisation studies, where genetically elevated BMI, but not WHR, was found to be causally associated with endometrial cancer risk . The mechanisms that may underlie the association of obesity with endometrial cancer are not fully characterised but likely include higher oestrogen levels in postmenopausal women, hyperinsulinaemia and a chronic inflammatory state .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, the International Agency for Research on Cancer recently deemed adiposity to be causal for endometrial cancer . Furthermore, our findings are in partial agreement with recent Mendelian Randomisation studies, where genetically elevated BMI, but not WHR, was found to be causally associated with endometrial cancer risk . The mechanisms that may underlie the association of obesity with endometrial cancer are not fully characterised but likely include higher oestrogen levels in postmenopausal women, hyperinsulinaemia and a chronic inflammatory state .…”
Section: Discussionsupporting
confidence: 89%
“…138 Furthermore, our findings are in partial agreement with recent Mendelian Randomisation studies, where genetically elevated BMI, but not WHR, was found to be causally associated with endometrial cancer risk. 139,140 The mechanisms that may underlie the association of obesity with endometrial cancer are not fully characterised but likely include higher oestrogen levels in postmenopausal women, hyperinsulinaemia and a chronic inflammatory state. 4,8,19,141,142 In our review, the evidence for an association between BMI and endometrial cancer was strong for premenopausal cancer, but was highly suggestive for postmenopausal disease due to large between-study heterogeneity, which could be due to a stronger association observed between BMI and endometrial cancer among neverusers than among ever-users of HRT (RR 1.90, 95% CI 1.56-2.30, and RR 1.18, 95% CI 1.07-1.31).…”
Section: Obesity and Endometrial Cancermentioning
confidence: 99%
“…Mendelian randomization (MR) is a well-documented application of instrumental variable (IV) methodology using genetic variants (most commonly, single-nucleotide polymorphisms [SNPs]) as IVs to provide relatively unbiased causal estimates of the effect of an exposure (i.e., BMI) on an outcome (i.e., mortality) (14,15). MR has provided evidence to support a causal effect of higher BMI increasing the risk of cardiovascular diseases (CVDs), diabetes, cardiometabolic traits, and various cancers (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). However, no study has explicitly used MR to explore the causal role of BMI in all-cause and cause-specific mortality.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Mendelian randomization studies point to a causal positive association between body mass index (BMI) and some cancers that have shown consistent associations with adiposity in observational studies. [5][6][7][8][9] The causal pathways for the T2D-cancer association are, however, far from established. It is not clear whether it is the metabolic changes (e.g., hyperglycemia or hyperinsulinemia) associated with T2D that affect cancer risk or whether the association is due to nonbiological factors or potentially shared risk factors for T2D and cancer.…”
mentioning
confidence: 99%